Efektifitas Pendidikan Kesehatan Melaui Media Video terhadap Perilaku Pencegahan Anemia pada Remaja Putri - Fenny Apriana Permatasari; Ernita Prima Noviyani; Ratna Wulandari (NERSMID : Jurnal Keperawatan dan Kebidanan, 2025)
The prevalence of anemia in adolescent girls in Riau Islands Province is 32%, which is equivalent to 3 to 4 out of every 10 adolescents experiencing anemia. However, routine monitoring and intervention programs targeting anemia in adolescent girls have not been implemented optimally. This study aims to determine the effectiveness of health education through video media on anemia prevention behavior in adolescent girls at SMPN 11 Bintan, North Bintan District, Bintan Regency, Riau Islands Province in 2024. This study used a pre-experimental method with a one-group pretest-posttest design. The population in this study were all 323 female students of SMPN 11 Bintan, with a sample of 76 female students selected using a simple random sampling technique. The instrument used was a questionnaire with a Likert scale. Data analysis included univariate analysis to describe data distribution and bivariate analysis using a paired t-test to test the hypothesis. The results showed that before the health education intervention, 63.2% of female students showed a moderate level of anemia prevention behavior, which increased to 76.3% after the intervention. The paired t-test produced a p value of 0.000 (<0.05), indicating a significant effect of health education through video media on anemia prevention behavior. It can be concluded that health education using video media is effective in improving anemia prevention behavior in adolescent girls at SMPN 11 Bintan.